Grooming and etiquette as part of nurse’s professionalism: An essential curricular competency: Grooming of Nurses - Safdar, Sachal Aqeel; Safdar, Lubna (Pakistan Journal of Medical Sciences, 2019)
Objective: The B.Sc. Nursing has limited hours dedicated to grooming and personal development. A smartly turned out, trained empathetic and efficient nurse helps in alleviating the miseries of the patients. The objective of this study was to see the acceptability and perceived usefulness of a course on grooming and etiquette.Methods: A proforma based qualitative study was carried out at College of Nursing, AFPGMI & National University of Medical Sciences (NUMS), Rawalpindi, from Jan to Dec, 2017. An eight week course, with weekly lectures was conducted for first to fourth year classes. At the end a semistructured proforma with simple open ended questions was administered. The questions were both in English and Urdu. The results were analyzed by finding percentages of positive and negative responses. The descriptive responses were grouped in recurring themes and analyzed for content and their constructive value.Results: There were 186 nursing cadets who completed the course and filled the proforma (55, 52, 45 and 34 from first year to fourth year, respectively). Out of 186, 98.9% (184) thought that this was a useful course. All topics were considered useful. Most liked were communication skills, teaching visits to wards, hostels and balancing home and work. About 7% disagreed about the strict dress codes, but agreed with the proper demeanor. Many suggested that senior nurses also have a dire need of these grooming lectures as many used derogatory language. Also pointed out was absence of a mechanism to report a lapse in ethical conduct seen in a colleague or a senior.Conclusion: Nursing is a demanding profession. It is important that our training includes sensitization to the non-technical attributes. They have to be groomed to become role models for young talented girls to join this noble profession. Even a short course may help to sensitize these young ladies to a very important aspect of their lives and profession.How to cite this:Safdar SA, Aqeel L. Grooming and etiquette as part of nurse’s professionalism- An essential curricular competency. Pak J Med Sci. 2019;35(2):404-408. doi: https://doi.org/10.12669/pjms.35.2.647This is an Open Access article distributed under the terms of the Creative Commons Attribution License (http://creativecommons.org/licenses/by/3.0), which permits unrestricted use, distribution, and reproduction in any medium, provided the original work is properly cited.